Multiphasic Prehabilitation Across the Cancer Continuum: A Narrative Review and Conceptual Framework - Santa Mina, Daniel; van Rooijen, Stefanus J.; Minnella, Enrico M.; Alibhai, Shabbir M. H.; Brahmbhatt, Priya; Dalton, Susanne O.; Gillis, Chelsia; Grocott, Michael P. W.; Howell, Doris; Randall, Ian M.; Sabiston, Catherine M.; Silver, Julie K.; et al. (Frontiers in Oncology, 2021)
The field of cancer survivorship has significantly advanced person-centered care throughout the cancer continuum. Within cancer survivorship, the last decade has seen remarkable growth in the investigation of prehabilitation comprising pre-treatment interventions to prevent or attenuate the burden of oncologic therapies. While the majority of evidence remains in the surgical setting, prehabilitation is being adapted to target modifiable risk factors that predict poor treatment outcomes in patients receiving other systemic and localized anti-tumour treatments. Here, we propose a multiphasic approach for prehabilitation across the cancer continuum, as a conceptual framework, to encompass the variability in cancer treatment experiences while adopting the most inclusive definition of the cancer survivor.